A Nanocrystalline POM@MOFs Catalyst for the Degradation of Phenol: Effective Cooperative Catalysis by Metal Nodes and POM Guests. Issue 12 (1st February 2018) - Zhong, Xiahua; Lu, Ying; Luo, Fang; Liu, Yiwei; Li, Xiaohui; Liu, Shuxia
Abstract: Crystalline POM@MOFs hybrids are very promising for catalysis, due to catalytically active polyoxometalates (POMs) dispersed at the molecular level, and enhanced stability of both POMs and metal‐organic frameworks (MOFs). Herein, PW12 was encapsulated into MOF HKUST‐1 through a facile liquid‐assisted grinding method, and the obtained [Cu2 (BTC)4/3 (H2 O)2 ]6 [HPW12 O40 ] (BTC=1, 2, 3‐benzenetricarboxylic acid) nanocrystals (NENU‐3N) were applied as catalysts in the degradation of phenol. It is the first time that liquid‐assisted grinding was applied in the preparation of nanocrystalline POM@MOFs hybrids. The NENU‐3N nanocrystals catalyzed the degradation of phenol on the basis of both MOF and POM catalytic activities, representing the first example of POM@MOFs catalyst boosting catalytic oxidation reaction with double actives sites. Strikingly, up to 97 % conversion and 88 % mineralization have successfully realized by perfect cooperative catalysis between POMs and Cu II nodes in MOFs at 35 °C. Moreover, comparative experiments suggest that the reduced size of NENU‐3N catalyst is beneficial for improving its catalytic performance. Finally, the nanocrystalline NENU‐3N catalyst possesses high stability, which can be easily recovered and reused 5 times without loss of catalytic activity. Abstract : Hybridization : PW12 @HKUST‐1 nanocrystals were prepared by encapsulating PW12 into MOFs HKUST‐1 through facile liquid‐assisted grinding method. The PW12 @HKUST‐1 nanocrystals cooperatively catalyzed the degradation of phenol on the basis of both MOF and POM catalytic activities. Strikingly, high conversion and mineralization have successfully realized by perfect cooperative catalysis between POMs and Cu II nodes in MOFs.